Substance misuse and cognitive functioning in early psychosis: A 2 year follow-up - McCleery, Amanda; Addington, Jean; Addington, Donald (Schizophrenia research, 2006)
High comorbidity exists between substance use and psychosis. Since substance use has been shown to negatively impact cognitive functioning in the general population, there is concern about the impact of substance use on already compromised cognitive functioning. However, the literature regarding the effects of substance use on cognition in early psychosis patients is inconclusive. The purpose of this study was to examine the relationship between substance misuse and cognitive functioning in a first episode psychosis sample for 2 years following admission to a specialized early psychosis program. One hundred and eighty-three subjects were assessed at baseline, 147 at 1 year and 116 at 2 years using the Case Manager Rating Scale (CMRS) for substance use and a comprehensive cognitive battery. Approximately 50% of subjects engaged in substance misuse at baseline, which did decrease over follow-up. At baseline, the cognitive performance of patients with both mild use and misuse was significantly better than non-users. These same patients demonstrated better performance at follow-up. These results do not provide evidence for a negative impact of substance use on cognition.